Diabetes care for people experiencing homelessness in the UK: insights from a national survey of frontline professionals and the development of an integrated care model - Oehring, Daniela; Paisi, Martha; Nasser, Mona; Jackson, Theo; Young, Ryan; Wooff, Lynne; Partridge, Helen; Conaty, Jacqueline; Dorney-Smith, Samantha (Frontiers in Public Health, 2025)
IntroductionPeople experiencing homelessness (PEH) face food insecurity, unstable housing and fragmented services that render conventional diabetes pathways unworkable and amplify complications.MethodsBetween January and April 2024, we conducted a nationwide, cross-sectional mixed-methods survey of front-line professionals via NHS, inclusion-health and voluntary-sector networks, analysing quantitative data (n = 104) with ANOVA, Kruskal–Wallis tests and ordinal logistic regression, and subjecting free-text responses to reflexive thematic analysis, before converging findings to develop the Integrated Holistic Diabetes Care Model for Homelessness (IHD-CMPH).ResultsRespondents comprised specialist diabetes clinicians (31%), homelessness/inclusion-health staff (38%) and VCSE providers (32%); median perceived Type 1 prevalence among PEH was 20% versus 8% nationally (p < 0.001). Fifty-seven per cent rated diabetes outcomes for PEH as poor or very poor, and 66% reported more frequent amputations and vision loss. Clear organisational policies (OR 1.62, 95% CI 1.06–2.48), cross-sector collaboration (OR 2.76, 1.20–6.36) and outreach-specific training (OR 2.50, 1.50–4.17) were independently associated with better outcomes. Thematic analysis highlighted service fragmentation, inflexible appointments and insufficient homelessness-specific education.DiscussionDiabetes inequities among PEH stem chiefly from modifiable structural failures rather than patient non-adherence. The novel IHD-CMPH, anchored in outreach and mobile screening, provides a scalable framework to operationalise inclusion-health policy, improve glycaemic surveillance and avert avoidable admissions; this first national study translating multi-sector front-line evidence into a coherent policy model offers concrete levers for health-system reform and equity advancement.